The Study of Fluid on Rayleigh-Taylor Instability Phenomena using Finite Volume Particle (FVP) Method - Nur Asiah Aprianti; Sparisoma Viridi; Zaki Su'ud; Koji Morata (Institut Teknologi Bandung, 2015)
Rayleigh-Taylor instability phenomena were encountered in science world, both on a small scale and large scale (interstellar gas). Rayleigh-Taylor instability is the interpenetration of material that occurs when a fluid is above the other fluid with smaller mass density. The fluid which was originally located in the upper part will continuously broke down and the void is filled by a fluid which was originally located in lower part, so it looks like a bubble. In computational fluid dynamic field, this phenomenon is one of the benchmarks used to test the performance of buoyancy force on a numerical method. On the particle method, particularly, the Rayleigh-Taylor instability has been successfully simulated using Moving Particle Semi-implicit (MPS) method. Similar to the MPS, on this study, the Rayleigh-Taylor instability between the silicon oil and water which driven by buoyancy force was simulated using finite volume particle (FVP) method. From the simulation results it can be concluded that the shape of the bubble produced in the present calculation is similar to the results observed in the experiments and methods of MPS.